2017
DOI: 10.1371/journal.pone.0182781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cancer-testis antigen, TFDP3, on cell cycle regulation and its mechanism in L-02 and HepG2 cell lines in vitro

Abstract: TFDP3, also be known as HCA661, was one of the cancer-testis antigens, which only expressed in human tissues. The recent researches about TFDP3 mostly focused on its ability to control the drug resistance and apoptosis of tumor cells. However, the role of TFDP3 in the progress of the cell cycle is rarely involved. In this study, we examined the expression of TFDP3 in human liver tissues firstly. After that, we detect the expression of TFDP3 at the RNA level and protein level in L-02 cell line and HepG2 cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…TFDP3 is a new transcription regulator of E2F, which can inhibit the binding and transcriptional activity of E2F with DNA. Jiao et al’s study indicated that the E2F/TFDP3 complex was involved in cell cycle regulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…TFDP3 is a new transcription regulator of E2F, which can inhibit the binding and transcriptional activity of E2F with DNA. Jiao et al’s study indicated that the E2F/TFDP3 complex was involved in cell cycle regulation [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most E2Fs, TFDP1 and TFDP2 are predominately nuclear, but E2F4 and E2F5 show cell cycle-specific localization ( 33 35 ). Furthermore, we found that subcellular location of TFDP3 is cell cycle specific, it is expressed in the nucleus in G1 phase and at the end of mitosis, in the cytoplasm in S phase and G2 phase ( 15 ). Thus, in quiescent cells, repressed E2F4 and E2F5 interacted mainly with TFDP1 or TFDP2, binding with E2F-targeted promoters and blocking the transcription of cell cycle-related genes.…”
Section: The Molecular Mechanisms Of Tfdp3mentioning
confidence: 95%
“…As expected, we verified that TFDP3 is expressed in the nucleus mainly at the end of mitosis phase, diffusively in G1 phase, and in the cytoplasm in G2 phase. Moreover, we detected that TFDP3 is highly expressed in S phase by Western blot of synchronous cells ( 15 ). Interestingly, a study of TFDP3 in prostate cancer emphasized that TFDP3 was coexpressed with E2F1.…”
Section: The Characterization and Expression Of Tfdp3mentioning
confidence: 97%
See 2 more Smart Citations